Aplicação de artes manuais na moda streetwear - Gonçalves, Julieth Stefany (2015)
This research aims to promote interaction between the popular and the modern. Join two important parts of the fashion culture that are totally opposite: manual techniques and streetwear. Driven by the perceived devaluation of the arts manuals and technical handmade by supporters of the current streetwear, manufacturing processes have been leaving scant relevance of manual techniques for fans of this group for both casual wear and for subsequent interest in learning. Consequently, ancient techniques that carry a significant part of the culture of each region being lost gradually in time. Through the design process, develop methods for the public concerned feel motivated, and then satisfied, to purchase a product containing manual features.